Key considerations for novel aptamer generation and aptasensor platform design: a case study on human Î±-thrombin and histamine as sensor targets - Ho, Lance St John (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2018)
Expected release date-April 2020
Keywords: Uncatalogued